(untitled) (Journal of Bio-Science, 2026)
The global prevalence of diabetes is increasing at an alarming rate, making its management a primary clinical concern. While conventional pharmacological treatments are effective, they are often associated with significant side effects. Consequently, research has shifted toward identifying safer, natural alternatives. This study investigates the antidiabetic and antihyperlipidemic potential of Chenopodium murale leaf (CML) extract in a mice model. The study utilized an acute toxicity test and an oral glucose tolerance test (OGTT) in healthy mice. Diabetes was induced via an intraperitoneal injection of streptozotocin (STZ). Diabetic mice were then treated with CML extract (200 and 400 mg/kg), metformin (150 mg/kg), or a vehicle control (0.5% CMC) for 15 days. Key parameters measured included blood glucose levels, body weight, and a complete lipid profile (TC, TG, LDL, and HDL). Additionally, liver function was assessed by measuring serum glutamate oxaloacetate transaminase (SGOT) and serum glutamate pyruvic transaminase (SGPT) levels. The extract was found to be safe up to a dose of 1000 mg/kg. Treatment with CML extract significantly improved glucose tolerance compared to the untreated diabetic group (both p<0.001 at 90 min). Both doses (200 and 400 mg/kg) produced a dose-dependent reduction in blood glucose levels (both p><0.001 vs. DC). Furthermore, the extract effectively lowered TC, TG and LDL cholesterol levels (400 mg/kg, p><0.001 vs. DC); while slightly increasing HDL cholesterol (400 mg/kg, p><0.01 vs. DC). A significant reduction in SGOT (200 & 400 mg/kg; p><0.01, p><0.001 vs. DC) and SGPT levels (400 mg/kg, p><0.05 vs. DC) also indicated potent liver protective effect. The CML extract exhibits significant glucose and lipid lowering efficacy alongside protect liver functions in diabetic mice, considered as a natural alternative for diabetes management. J. Bio-Sci. 34(1): 31-40, 2026